OUTDOOR LEARNING: EDU FARM ACTIVITY DALAM MENINGKATKAN KECERDASAN NATURALISTIK ANAK USIA DINI - Kamil, Nurhusna; Narjis, Khalilah; Zahrah, Faiqatuz; Arnisa Harahap, Fadila (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2024)
This research is motivated by the fact that many schools facilitate outdoor learning activities as a means of developing naturalistic intelligence. Therefore, this research will examine whether Edu Farm is indeed effective if used as a way to increase naturalistic intelligence in young children in group B at the Sungai Rumbai Islamic Kindergarten. The research method used was qualitative with a case study approach on a sample of 12 children. Data collection was carried out by carrying out the observation and documentation stages. For data analysis using the Miles & Huberman technique which consists of 3 stages, namely data reduction, data presentation and drawing conclusions. The results of this research contribute to educators as an alternative to realizing naturalistic intelligence in early childhood by utilizing the surrounding environment as a means of education. Apart from that, from the research that has been carried out, information has been obtained that this activity can increase children's intelligence and build their knowledge through fun activities involving interactive activities. The latest in this research is that children are given the freedom to interact directly with farm animals. Apart from that, usually edu farm activities tend to be carried out at zoos, but this research carried out direct visits to livestock pens located around residents' homes.